Citizenship Competencies to Counter Bullying in Cartagena, Colombia - Domínguez-de la Ossa, Elsy; Vázquez-Miraz, Pedro; Fortich-Pérez, David; Campo-Landines, Kiara (Revista Electrónica Educare, 2024)
Introduction. This paper explores the scope of a pedagogical intervention aimed at promoting citizenship competencies as a strategy for bullying prevention in schools in Cartagena, Colombia. Objective. A quantitative study was conducted with 47 elementary school students from three educational institutions (E.I.). The students were evaluated using the CIE-A questionnaire to determine the levels of victimization, intimidation, and symptoms associated with bullying, as well as to identify differences among students according to sociodemographic variables. Methodology. Global levels of bullying were measured in three educational institutions in Cartagena de Indias (N = 1.085), Colombia. Then, the grades with the highest scores in each school were selected. Finally, a pedagogical intervention comprising fifteen interactive didactic workshops was conducted to reduce bullying levels to make a pre- and post-treatment comparison with the people who completed all the activities (N = 47) and identify differences based on sociodemographic variables such as age, sex, or the school to which they belonged. Results. The initial results showed extreme levels of bullying in the three selected classes. These values decreased after the implementation of the didactic activities. More specifically, notable improvements were evidenced at a statistical level in the bullying subfactor denominated as victimization, the didactic workshops having been more effective in male children of younger age and coming from the E.I. that had a greater number of attendees. Conclusions. The data obtained suggest that promoting citizenship competencies is an adequate formative strategy to mitigate extreme bullying in vulnerable contexts. However, new pedagogical strategies are needed for more specific groups that did not show relevant improvements in the present research, such as students with repeated grades and low classroom attendance.